(untitled) (Scientific journal of the Fergana State University, 2023)
Today, modern schools need teachers with promising teaching technologies, and on the other hand, innovative and interactive methods of teaching students studying in higher education, and sufficient knowledge on the practical application of modern technologies. Is explained by the fact that they do not have qualifications. Methodological competence of a teacher is related to the experience of using teaching technology, innovative teaching methods and methods in university practice, and is a set of psychological, pedagogical and methodological knowledge, skills and abilities. Pedagogical conditions for improving the process of developing methodical competence of future teachers of technology and ways of effectively organizing lessons are covered in the article.